If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 1) = 7 Reorder the terms: x(1 + x) = 7 (1 * x + x * x) = 7 (1x + x2) = 7 Solving 1x + x2 = 7 Solving for variable 'x'. Reorder the terms: -7 + 1x + x2 = 7 + -7 Combine like terms: 7 + -7 = 0 -7 + 1x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '7' to each side of the equation. -7 + 1x + 7 + x2 = 0 + 7 Reorder the terms: -7 + 7 + 1x + x2 = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 1x + x2 = 0 + 7 1x + x2 = 0 + 7 Combine like terms: 0 + 7 = 7 1x + x2 = 7 The x term is 1x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. x + 0.25 + x2 = 7 + 0.25 Reorder the terms: 0.25 + x + x2 = 7 + 0.25 Combine like terms: 7 + 0.25 = 7.25 0.25 + x + x2 = 7.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 7.25 Calculate the square root of the right side: 2.692582404 Break this problem into two subproblems by setting (x + 0.5) equal to 2.692582404 and -2.692582404.Subproblem 1
x + 0.5 = 2.692582404 Simplifying x + 0.5 = 2.692582404 Reorder the terms: 0.5 + x = 2.692582404 Solving 0.5 + x = 2.692582404 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 2.692582404 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 2.692582404 + -0.5 x = 2.692582404 + -0.5 Combine like terms: 2.692582404 + -0.5 = 2.192582404 x = 2.192582404 Simplifying x = 2.192582404Subproblem 2
x + 0.5 = -2.692582404 Simplifying x + 0.5 = -2.692582404 Reorder the terms: 0.5 + x = -2.692582404 Solving 0.5 + x = -2.692582404 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -2.692582404 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -2.692582404 + -0.5 x = -2.692582404 + -0.5 Combine like terms: -2.692582404 + -0.5 = -3.192582404 x = -3.192582404 Simplifying x = -3.192582404Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.192582404, -3.192582404}
| 23-(-10)+(-19)= | | 10d-22+6d=12d+12 | | 23x=85 | | 3(x)=5(y)-11 | | -3(6n+4)=24 | | y/2+3=2(y-2) | | 7k-2k=25 | | 3C+9=-24 | | x^2=2x+13 | | -3(x+5)+2(x+8)=35 | | t/8-6=-12 | | 2[7-7(1-n)]+4n=-16+3[6(n+1)-3n] | | 5b^2-35b+60=0 | | 12(11p+11)+11p=275 | | 4=3(-1)-1 | | 16+7-4x=3 | | 4x+3=7x | | 5x=y-4 | | 4+a=9 | | 0.40(y+10)-0.60(y+2)=2 | | 15(14-14x)+3(9+7x)=48 | | 36=2(w*3)+2w | | -7(-5b+4)=-28 | | -9x^2+36x=38 | | 9+y/5=6 | | 2(6c-1)-18=10c+2 | | -4.905x^2-1.11x+0.8=0 | | 4x-13x-x=-150 | | 4(p+3)=4 | | -3(4x+1)+3x= | | 2m-2= | | 4-16p=(3-2p)4 |